Removal of per- and polyfluoroalkyl substances from contaminated groundwater by granular activated carbon and anion exchange resins: a pilot-scale comparative assessment. Issue 10 (15th August 2022) - Liu, Charlie J.; Murray, Conner C.; Marshall, R. Eric; Strathmann, Timothy J.; Bellona, Christopher
Abstract : Granular activated carbon (GAC) and anion exchange resins (AERs) were evaluated for PFAS removal and compared based on treatment performance and cost. Abstract : Granular activated carbon (GAC) and anion exchange resins (AER) are commonly used for the remediation of per- and polyfluoroalkyl substances (PFASs). This contribution reports on a continuous-flow pilot-scale system operated for ∼1 year to evaluate and compare adsorption of 9 PFASs in contaminated groundwater by one GAC and three AERs operated at 10 and 2.5 min empty bed contact times, respectively, at the same column flowrates. Breakthrough of individual perfluorocarboxylic acids (PFCAs) and perfluorosulfonic acids (PFSAs) for GAC and PFCAs for AERs were influenced by compound chain length. However, breakthrough of PFSAs for all AERs occurred at the same time, possibly due to AER fouling by metals present in the source groundwater. Adsorption trends and capacity were similar amongst the three AERs evaluated. Dissolved organic carbon (DOC) was continuously removed by GAC and AERs and anionic species were not shown to be appreciably removed by AERs. Comparisons between GAC and AER were evaluated based on treatment efficacy and estimated operational costs. For comparison metrics influenced by media mass or volume including bed volumes treated, mass of PFAS adsorbed per media mass, and mass of media used per volume of water treated, AERs adsorbed 6–7 times more PFASs than GAC. However, based on volume of water treated where the columns were operated at the same flowrate, AERs performed similarly to GAC for PFCAs and better than GAC for PFSAs. Breakthrough of PFCAs will likely dictate media changeout due to the earlier breakthrough of PFCAs compared to PFSAs. GAC and AERs treated similar volumes of water prior to breakthrough of PFCAs suggesting that GAC and AER may be similarly effective PFAS treatment technologies. For AER and GAC O&M costs to be similar, the ratio of AER to GAC unit media costs was ∼3.5.